Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M134/2 - Nikolas Stange; Heiko Sahling (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Kongsberg EM122 multibeam echosounder during the RV METEOR cruise M134/2. The cruise took place between 2017-02-19 and 2017-02-26 (Punta Arenas, Chile – Valparaiso, Chile). The main objective of the cruise M134/2 was to perform continuous measurements of methane and carbon dioxide in the air along the cruise track. In addition, bathymetric mapping was carried out along the convergent continental margin off Chile. Sound velocity profiles (SVP) are integrated into the raw .all files. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).